Development of an Indonesian Language Learning Evaluation E-Module Containing Papuan Local Wisdom Values to Improve Student Competence at Victory University Sorong - Irwan Soulisa; Dinda Irdayani Soulisa; Helena Paula Burdam (LP. Ma'arif Janggan Magetan, 2026)
Indonesian language education in higher education plays a strategic role in developing students' critical, communicative, and reflective thinking skills as future educators and academics. However, observations in the Indonesian Language Learning Evaluation course at Victory University Sorong indicate that students limited in understanding the concepts, principles, and application of evaluation instruments contextually. This study aims to develop an Indonesian Language Learning Evaluation E-Module based on Papuan local wisdom that can improve the pedagogical and professional competence of Victory University Sorong students. This study uses a RnD approach with the ADDIE model. The results of the study indicate that the development of an e-module based on Papuan local wisdom has proven valid, practical, and effective in improving student competency. The eligibility criteria with an average expert validity value of 0,90, a practicality level of 88,4%, and significant effectiveness based on the ANCOVA statistical test (p < 0,001) and a large effect size (Hedges' g = 0,86). The findings of this research contribute to the development of innovative learning media based on local culture in the digital era and strengthen the vision of Victory University Sorong as a higher education institution rooted in local wisdom values and oriented towards regional excellence.